2022
DOI: 10.11604/pamj.2022.41.21.29932
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of primary health care workers´ knowledge and skill for COPD and asthma screening and diagnosis in Jos LGA of Plateau State

Abstract: Introduction chronic obstructive pulmonary disease and asthma are the commonest of the group of Chronic Respiratory Diseases. Primary Health Care workers play a role in the prevention of these diseases. The aim of this study was to determine the knowledge and diagnostic skills of PHC workers on COPD and asthma in a local government area of Plateau State, Nigeria. Methods it was a cross-sectional study conducted among 146 primary healthcare workers selected through a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…3-31.5). This result was consistent with a research carried out in Nigeria (26.1%) [9]. However, this was considerably less than research conducted in India (69%) [19].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…3-31.5). This result was consistent with a research carried out in Nigeria (26.1%) [9]. However, this was considerably less than research conducted in India (69%) [19].…”
Section: Discussionsupporting
confidence: 92%
“…According to this study, HWT practice was found to be 14.1% . This self-reported study's prevalence of HWT practice (14.1%) was much lower than studies carried out in India (53%), Zambia (50%), Nigeria (54%), and Kenya (69%) [9,[19][20][21], respectively. The disparity may result from different coverage of clean water as well as different household-level water treatment options across the nation depending on people's knowledge of the availability and quality of water.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations